Proyecto de emprendimiento - viabilidad para la creación de la empresa "Mila" (2018)
The present project, shows a viabiliaibility study for the creation of a company of relaxing aromatizers based on essential oils, located in the city of Bogotá. It was carried out through a diagnosis and study of markets, in order to identify the current state of the country against the production of essential oils and its commercialization for use in aromatherapy, in order to identify the target market, and thus determine the supply and demand.